Influence of the phytoplankton community structure on the spring and annual primary production in the northwestern Mediterranean Sea - Mayot, N.; D'Ortenzio, F.; Uitz, J.; Gentili, B.; Ras, J.; Vellucci, V.; Golbol, M.; Antoine, David; Claustre, H. (Wiley-Blackwell Publishing, 2017)
Satellite ocean color observations revealed that unusually deep convection events in 2005, 2006, 2010, and 2013 led to an increased phytoplankton biomass during the spring bloom over a large area of the northwestern Mediterranean Sea (NWM). Here we investigate the effects of these events on the seasonal phytoplankton community structure, we quantify their influence on primary production, and we discuss the potential biogeochemical impact. For this purpose, we compiled in situ phytoplankton pigment data from five ship surveys performed in the NWM and from monthly cruises at a fixed station in the Ligurian Sea. We derived primary production rates from a light photosynthesis model applied to these in situ data. Our results confirm that the maximum phytoplankton biomass during the spring bloom is larger in years associated with intense deep convection events (+51%). During these enhanced spring blooms, the contribution of diatoms to total phytoplankton biomass increased (+33%), as well as the primary production rate (+115%). The occurrence of a highly productive bloom is also related to an increase in the phytoplankton bloom area (+155%) and in the relative contribution of diatoms to primary production (+63%). Therefore, assuming that deep convection in the NWM could be significantly weakened by future climate changes, substantial decreases in the spring production of organic carbon and of its export to deep waters can be expected.